A combined Monte Carlo/DFT approach to simulate UV-vis spectra of molecules and aggregates Merocyanine dyes as a case study - Tirri, Bernardino (Journal of computational chemistry, 2021)
© 2021 The Authors. Journal of Computational Chemistry published by Wiley Periodicals LLC.